Religiosity and Tax Compliance: Does Tax Knowledge Matter? - Delaviansyah, Dheva; Fitriana, Vita Elisa; Santosa, Setyarini (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2022)
This research examines the influence of religiosity on tax compliance and whether tax knowledge moderates the relationship between religiosity and tax compliance. This research used a quantitative approach. Purposive sampling was used as the sample collection method. The questionnaires were distributed electronically to 124 taxpayers domiciled in Karawang. The statistical analysis used in this research is structural equation modeling. The results show that religiosity has a significant positive effect on tax compliance. Furthermore, it moderated the role of tax knowledge on the relationship between religiosity and tax compliance. Therefore, the tax knowledge variable can strengthen the relationship between religiosity and tax compliance. The result highlighted the importance of conducting tax socialization which in turn imposes on tax knowledge. If the taxpayer has a good understanding of the tax rules and procedures, it will encourage compliance.